2010
DOI: 10.1590/s0101-31222010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Condutividade elétrica em sementes de rúcula

Abstract: RESUMO -O teste de condutividade elétrica da solução de embebição é recomendado para avaliar o vigor de sementes de ervilha e indicado para outras espécies, mas ainda há necessidade da continuidade de estudos sobre o assunto. A pesquisa teve como objetivo estabelecer ajustes na metodologia do teste de condutividade elétrica para avaliar o potencial fisiológico de sementes de rúcula (Eruca sativa L.). Para isso, o estudo foi conduzido utilizando dois cultivares de sementes de rúcula, Cultivada e Folha Larga, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
1
1
3
Order By: Relevance
“…Increase in leaching values was observed. These results are similar to those observed by Torres and Pereira (2010) in arugula seeds. The leachate values decreased as the water volume increased in the test a fact attributed to the dilution caused by the increase in the amount of water used to imbibe the seeds.…”
Section: Resultssupporting
confidence: 92%
“…Increase in leaching values was observed. These results are similar to those observed by Torres and Pereira (2010) in arugula seeds. The leachate values decreased as the water volume increased in the test a fact attributed to the dilution caused by the increase in the amount of water used to imbibe the seeds.…”
Section: Resultssupporting
confidence: 92%
“…Kappes et al (2009), analyzing the soybean seeds physiological potential, M-Soy 8866 variety, dried with diquat and paraquat in Santa Carmem location, Mato Grosso north, in 2006/2007 agricultural year, verified the dried lots with paraquat, compared to the control batch without desiccant, presented better performance in some of the quality tests used. Radke et al (2018) concluded that the electric conductivity tests in the combination of 50 seeds with 50 ml of water during 24 hours of imbibition were efficient to stratify lots of chia seeds with different vigor levels, they obtained values with ranges from 575.4 to 759.9 μS cm -1 g -1 (EC), values far from those found in this work, in which 100 ml of water was used for imbibition, which is explained by Torres and Pereira (2010) who work with arugula seeds, claim that the leachate values decreased as the volume of water increases, a fact attributed to the dilution caused by the increase in the amount of water used to imbibe the seeds. Kappes et al (2012) mention that, a general way the delay in drying, of the application provided a vigor reduction, probably due the longer time the seeds are in the field during the physiological maturation process.…”
Section: Resultscontrasting
confidence: 61%
“…Alguns pesquisadores vêm buscando a padronização do teste de condutividade elétrica para avaliação do vigor de sementes de hortaliças, conforme trabalhos realizados com pimenta (VIDIGAL et al, 2008), rúcula (ALVES; SÁ, 2009;TORRES;PEREIRA, 2010) e com jiló (LOPES; BARBOSA; VIEIRA, 2012). No entanto, para sementes de coentro, não há na literatura informações sobre metodologia específica para condução desse teste.…”
unclassified